INTEGRATED SUSTAINABLE MANGROVE FOREST MANAGEMENT - Cecep Kusmana (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
Mangrove forest as a renewable resource must be managed based on sustainable basis in which the benefits of ecological, economic and social from the forest have to equity concern in achieving the optimum forest products and services in fulfill the needs of recent generation without destruction of future generation needs and that does not undesirable effects on the physical and social environment. This Sustainable Forest Management (SFM) practices needs the supporting of sustainability in the development of social, economic and environment (ecological) sounds simultaneously, it should be run by the proper institutional and regulations. In operational scale, SFM need integration in terms of knowledge, technical, consultative of stakeholders, coordination among sectors and other stakeholders, and considerations of ecological inter-relationship in which mangroves as an integral part of both a coastal ecosystem and a watershed (catchment area). Some tools have been developed to measure the performent of SFM, such as initiated by ITTO at 1992 and followed by Ministry of Forestry of Indonesia (1993), CIFOR (1995), LEI (1999), FSC (1999), etc., however, the true nuance of SFM’s performance is not easy to be measured.